2015
DOI: 10.13189/ujer.2015.030807
|View full text |Cite
|
Sign up to set email alerts
|

Storytelling, Values and Perceived Resilience among Chinese, Vietnamese, American and German Prospective Teachers

Abstract: Numerous qualitative studies, mostly with English speaking Westerners, have shown the important role of storytelling and values in promoting resilience. However, this quantitative study helps fill the gaps in the research, by investigating the mediator effects of storytelling on values and resilience of American, German, Chinese, and Vietnamese prospective teachers. The study, using path analysis, investigated how cultural differences influenced perceptions about storytelling, resilience and values. Open to ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 26 publications
1
5
0
2
Order By: Relevance
“…For example, Liem et al (2011) found all ten first order and all four second order values in samples from Australia, Indonesia, Philippines, and Singapore. Plus, Stanley et al (2015) studied prospective teachers from China, Germany, Vietnam, and the U.S. Their results using the PVQ are consistent with much cross-cultural research. The Eastern cultures of China and Vietnam tend more to preferences for the values of Conformity, Achievement, Power, and Security.…”
Section: Valuessupporting
confidence: 70%
See 1 more Smart Citation
“…For example, Liem et al (2011) found all ten first order and all four second order values in samples from Australia, Indonesia, Philippines, and Singapore. Plus, Stanley et al (2015) studied prospective teachers from China, Germany, Vietnam, and the U.S. Their results using the PVQ are consistent with much cross-cultural research. The Eastern cultures of China and Vietnam tend more to preferences for the values of Conformity, Achievement, Power, and Security.…”
Section: Valuessupporting
confidence: 70%
“…Bréchon and Gonthier 2017; Halman et al 2011; Halman and Voicu 2010; Kaasa et al 2013, 2014; Matei and Abrudan 2018; Pettersson and Esmer 2008) World Values Survey (WVS) (Amoranto et al 2010; Basáñez and Inglehart 2016; Beugelsdijk and Welzel 2018; Dalton and Welzel 2014; Dobewall and Rudnev 2014; Fischer and Schwartz 2011; Gore et al 2019; Hofstede 1997; Inglehart 2018; Inglehart 2003; Inglehart and Welzel 2010; Johnson and Mislin 2012; Korotayev et al 2019; Matei and Abrudan 2018; Minkov and Hofstede 2012a, 2012b; Vauclair and Fischer 2011; Welzel 2010) Schwartz Value Survey (SVS) (Bardi and Goodwin 2011; Boer and Fischer 2013; Daniel et al 2015; Danis et al 2011; Dobewall and Rudnev 2014; Fischer et al 2011; Fischer and Schwartz 2011; Fischer et al 2010; Gollan and Witte 2014; Hanel et al 2018; Kasser 2011; Knafo et al 2011; Korotayev et al 2019; Lee et al 2011; Rudnev et al 2018; Schwartz 2012; Schwartz 1992, 2004, 2011b, 2011a, 2014, 2016; Schwartz and Sagiv 1995; Smith 2011; Vaisey and Miles 2014; van Herk and Poortinga 2012; Vauclair and Fischer 2011; Vauclair et al 2015; 2011; Welzel 2010al. 2016; Bender and Chasiotis 2011; Bilsky et al 2015; Bilsky et al 2010; Boer and Fischer 2013;Caprara et al 2017;Cieciuch et al 2013;Wet et al 2019;Fischer and Schwartz 2011;Güngör et al 2012;He et al 2017;Holtschlag et al 2013;Liem et al 2011;Lilleoja et al 2016;Robinson 2013;Rudnev et al 2018;Sandy et al 2014;Sanrı and Goodwin 2013;Schiefer 2013;Schiefer et al 2010;Schwartz et al 2001;Simón et al 2017;Sørensen et al 2012;Stanley et al 2015;Tulviste et al 2014;Vecchione et al 2012; Vyrost et al al. 2007;Dickson et al 2012;Dorfman et al 2012;House et al 2013; House and Hanges 2004;Kabasakal et al 2012;Mendenhall et al 2012;Mittal and Dorfman 2012;Stankov 2015;Steers et al 2012;Takahashi et al 2...…”
mentioning
confidence: 99%
“…Theme 3: The notion of positive adaptation is inherent in the concept of resilience (Luthar, 2006), but very few of the studies included in this analysis reported positive outcomes, and those that reported resilience-related outcomes provided little information about the process or mechanism of resilience (Hou, Law, Yin, & Fu, 2010; Stanley et al., 2015) (Table 3). There were inconsistencies in the conceptualization and measurement of the construct.…”
Section: Resultsmentioning
confidence: 99%
“…Significant and positive relations between these two profiles have demonstrated that highly optimist individuals report a more resilient profile than lowly optimist ones (Sagone & De Caroli, in press), whereas very little evidence referring to the influence of value orientations on resilience and dispositional optimism have been verified in adolescents and young adults, also taking into consideration the cultural differences linked to value priorities (see Maercker et al, 2015;Stanley et al, 2015). The lack of data on these relations represents the rationale of this current study carried out with healthy Sicilian adolescents; so, it will be necessary to verify the existence of the relationships among these constructs and then to explore the direction of the influence of value priorities on resilience and dispositional optimism also in young adults and older people.…”
Section: Introductionmentioning
confidence: 99%